The relaxation of a magnetically orientated liquid crystalline polymer - Assender, H; Windle, A (1996)
The relaxation of the orientation induced by the action of a magnetic field on a thermotropic liquid crystalline polymer is examined. The polymer is a main-chain random copolyester available as a molecular weight series covering the range 4600-14 400. The rate of loss of orientation is modelled using a similar function to that used to describe the orientation process, all induced orientation being lost over a period of 30 min. Microstructural studies show the complete loss of the domain structure developed on magnetic orientation, and also indicate that the orientation and relaxation cycle gives a microstructure which is coarser than that in the untreated samples. The influence of the crystallization process on the induced orientation is also examined.